Analysis on Fungal Diversity in Rhizosphere Soil of Continuous Cropping Potato Subjected to Different Furrow-Ridge Mulching Managements - Qin, Shuhao; Yeboah, Stephen; Xu, Xuexue; Liu, Yuhui; Yu, Bin (Frontiers in Microbiology, 2017)
Knowledge about fungi diversity following different planting patterns could improve our understanding of soil processes and thus help us to develop sustainable management strategies. The objective of this study was to determine the impact of different furrow-ridge mulching techniques on fungal diversity in rhizosphere soil under continuous cropping system. The investigated treatments were: flat plot without mulch (CK); flat plot with mulch (T1); on-ridge planting with full mulch (T2); on-furrow planting with full mulch (T3); on-ridge planting with half mulch (T4); and on-furrow planting with half mulch (T5). NGS (Illumina) methods and ITS1 sequences were used in monitoring fungi diversity of the potato rhizosphere soil. The fungi diversity in the rhizosphere soil was ranked in the order T5>T2>T4>T1>CK at the early growth stage and T2>T3>T1>T4>CK at the late growth stage of potato. The fungal communities found in the rhizosphere soil were Ascomycota, Zygomycota, Basidiomycota, Chytridiomycota and other unidentified fungal communities. Among the fungal community in the rhizosphere soil, Ascomycota was found to be dominant fungi population, with the highest percentage (89%) in the T5 soil whereas the T2 soils had the lowest percentage (67%). The Fusarium abundance in fully mulched treated soils was higher than in half mulched treated soil. The dominant genus in the T4 soil was Mortierella, whereas lower populations (1-2%) of Scutellinia, Cryphonectria, Acremonium and Alternaria were found in that treatment. Among the eumycetes, the dominant fungal class in all treated soils was the Sordariomycetes, which ranged from 57% to 85% in T2 and T5 soils, respectively. The Fusarium percentages in half mulched treated soils (T4, T5) were 55% and 28% lower than that of complete mulched treated soils (T2, T3), respectively. The cluster analysis results showed that, CK, T4 and T5 treated soils and T1, T2 and T3 treated soils had similarities in microbial compositions, respectively. Potato tuber yield was greater under the on-ridge planting with full mulch (T2) treated soil, followed by on-ridge planting with half mulch (T4) treated soil. The rhizosphere soil under the on-ridge planting with full mulch (T2) soil had the highest fungal diversity, suggesting that this management was the best environment